Functionalized cellulose nanocrystals as the performance regulators of poly(β-hydroxybutyrate-co-valerate) biocomposites. (15th August 2020) - Chen, Jianxiang; Yang, Runmiao; Ou, Junfei; Tang, Chuang; Xiang, Meng; Wu, Defeng; Tang, Juntao; Tam, Kam C.
Highlights: Hydrophilicity of CNC was successfully regulated. Functionalized CNC had heterogeneous nucleation effect on PHBV. Functionalized CNC restricted the chain mobility and diffusion of PHBV. Compatibility between functionalized CNC and PHBV was better. Functionalized CNC can improve the tensile and rheological properties of PHBV. Abstract: To investigate the relationship between functional groups on cellulose nanocrystals (CNC) and the performance of poly( β -hydroxybutyrate- co -valerate) (PHBV), the surface of CNC was modified by surface graft modification and PHBV/CNC biocomposites were prepared by melt blending. To demonstrate the interfacial adhesion difference between hydrophobic PHBV and hydrophilic CNC, palmitoyl chloride and ε -caprolactone had been used to tailor the oleophilic property of CNC. Results showed that CNC had heterogeneous nucleation effect on the crystallization process of PHBV, while the entanglement of molecular chains weakened the promoting functions of CNC- g -C16 (CNC grafted with palmitoyl chloride) and CNC- g -CL (CNC grafted with ε -caprolactone). Furthermore, CNC- g -CL exhibited better interfacial adhesion with PHBV when compared with CNC- g -C16. And 1 wt% CNC- g -CL improved the tensile strength of PHBV biocomposite to 38.09 MPa, which is 26.25% higher than PHBV.